Pushing against the boundaries: Entertaining impoliteness and taboo discourse in the Egyptian TV show Abla Fahita - Ibrahim Wesam M. A. (De Gruyter, 2021)
Impoliteness can be defined as the use of “communicative strategies” which are “designed to attack face, and thereby cause social conflict and disharmony” (Culpeper et al. 2003, 1564). The present study applies Jonathan Culpeper’s (2011a) model of “impoliteness” supplemented by the notions of jocular mockery, jocular abuse, and recipients’ responses (Bousfield 2008, 2010, Haugh and Bousfield 2012) to the Egyptian TV show Abla Fahita. Abla Fahita (Egyptian Arabic: أبلة فاهيتا‎ [ʾabla fāhīta]) is a puppet character that has regularly appeared on Egyptian television since 2011. The show is hugely popular and has been phenomenally successful, being watched on average by millions, according to the Egyptian Centre for Research on Public Opinion. It should be noted, however, that, due to the conservative nature of Egyptian culture, Abla Fahita and other similar TV shows are considered to violate Egyptian politeness standards radically. Hence, such shows have been condemned as degrading and of low moral standards and have been accused of causing a deterioration in the standards of Egyptian public taste. Despite all denunciations, Abla Fahita still enjoys a huge audience and dominates broadcast ratings. Part of the show’s popularity can be ascribed to its characteristic impoliteness, particularly Abla Fahita’s off-beat expressions in mocking her guests and her use of sexual innuendo, which is seen as entertaining by many viewers. The study, which reveals that Abla Fahita employs what can be called a humorous-impoliteness formula to entertain viewers, is an attempt to apply contemporary Impoliteness Theory across cultures, and to Colloquial Egyptian Arabic in particular.